Living in Rural Areas of Peninsular Malaysia: Risk Factor for Goitre - MA, Shahar; AM, Omar; N, AB Wahab; N, Sukor; NA, Kamaruddin (IIUM Medical Journal Malaysia, 2019)
Introduction: Thyroid disorders are among common medical conditions encountered in clinical practice. However, the disease burden among Malaysian population has not been established. This study was aimed to determine the prevalence of goitre and its associated factors among adult population in Peninsular Malaysia. Materials and Methods: A cross-sectional study was performed in 5 pre-assigned regions in Peninsular Malaysia. Participants’ sociodemographic profile and medical history were recorded. Physical examinations were done looking for abnormalities of the thyroid gland and signs of thyroid dysfunctions. The diagnosis of goitre was made by palpation and corroborated by the repeat examination by another investigator. The World Health Organization (WHO) goitre grading system was used. Fifteen millilitre of blood were withdrawn and analysed at a central laboratory. Results: Among 2190 respondents, the prevalence of goitre was 9.3%. Goitre was associated with positive anti-thyroperoxidase and anti-thyroglobulin antibodies. Females were at higher risk of goitre (adjusted OR = 2.4; 95% CI 1.6–3.5; p<0.001). The other risk factors of goitre were Indian ethnicity (adjusted OR=2.0; 95%CI 1.2–3.3; p=0.006), positive anti-thyroperoxidase (adjusted OR=1.8; 95% CI 1.1-3.1; p=0.024) and living in rural area (adjusted OR = 1.7; 95% CI 1.2–2.5; p=0.002). These areas had been shown to suffer from some degree of iodine insufficiency in the past. Conclusions: The prevalence of goitre in Peninsular Malaysia was comparable with other studies. The main predictors of thyroid disorders are female gender and thyroid antibodies. Living in rural areas was associated with goitre. ><0.001). The other risk factors of goitre were Indian ethnicity (adjusted OR=2.0; 95%CI 1.2–3.3; p=0.006), positive anti-thyroperoxidase (adjusted OR=1.8; 95% CI 1.1-3.1; p=0.024) and living in rural area (adjusted OR = 1.7; 95% CI 1.2–2.5; p=0.002). These areas had been shown to suffer from some degree of iodine insufficiency in the past. Conclusions: The prevalence of goitre in Peninsular Malaysia was comparable with other studies. The main predictors of thyroid disorders are female gender and thyroid antibodies. Living in rural areas was associated with goitre.